Implementasi Kebijakan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Desa Koili Kecamatan Bunta Kabupaten Banggai - Annisa Cahyani Kartika; Rustam Tohopi; Yacob Noho Nani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The problem addressed in this research is the suboptimal implementation of the Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) in Koili Village. The objective of this research is to analyze the implementation of the PAMSIMAS Program based on Donald P. Warwick’s policy implementation theory, which includes organizational capacity, information, support, and the distribution of potential resources. This research employs a descriptive qualitative method. Data were collected through interviews, observations, and documentation involving informants from the local government, village officials, PAMSIMAS management, and community members, both beneficiaries and non-beneficiaries. The findings indicate that the PAMSIMAS Program has been implemented; however, it has not yet been fully optimized. Organizational capacity and information dissemination have been implemented, but limitations remain in implementers’ capacity and in the equitable distribution of information. Support from the village government and the community is relatively good; nevertheless, coordination and the distribution of potential resources still need improvement. This research recommends that future researchers examine the implementation of PAMSIMAS on a broader regional scale and incorporate a more in-depth analysis of sustainability and community participation.